Long-term safety and efficacy of infliximab for the treatment of ankylosing spondylitis - Elalouf O; Elkayam O (Dove Medical Press, 2015)
Ofir Elalouf, Ori Elkayam Department of Rheumatology, Sackler Faculty of Medicine, Tel Aviv Medical Center, Tel Aviv, Israel Abstract: The introduction of TNFα blockers has revolutionized the treatment of ankylosing spondylitis (AS). The objectives of this review are to summarize the most up-to-date data on long-term efficacy and safety of infliximab in AS, with special emphasis on axial and extra-articular disease, predictors of response, and radiological response. The general consensus of this literature search was that infliximab is highly efficacious in the treatment of AS. Most studies have demonstrated good clinical outcomes after 3 years of treatment, as measured by Spondyloarthritis International Society response in 75%–85% of treated AS patients. Reports on the long-term effects of infliximab as documented by radiological findings, however, are controversial. While some studies reported a similar progression rate as that of the historical OASIS cohort, others have suggested that infliximab may halt new bone formation. The long-term safety of infliximab is well known, mainly from data stored in national registries. While it has been suggested that side effects of infliximab may be fewer in AS compared to rheumatoid arthritis, data on this issue are sparse, with most of the information on long-term safety pertaining to rheumatoid arthritis. It can however be concluded that the long-term efficacy of infliximab is apparently maintained in AS and with an acceptable safety profile. Keywords: spondylitis, long-term efficacy, safety, TNFα blockers